2018
DOI: 10.1021/acs.jpcc.8b06506
|View full text |Cite
|
Sign up to set email alerts
|

Seeking a Structure–Function Relationship for γ-Al2O3 Surfaces

Abstract: The surface of γ-Al 2 O 3 is perhaps the most exploited surface in chemistry. It is used as a catalyst and as a catalyst support. Its porosity is often evoked as the key quality of this material. However, an atomic-level understanding of this system has yet to be achieved, in most part because of the plethora of microscopic realizations of this surface. The atomic-level understanding of γ-Al 2 O 3 surfaces is arguably essential to predict and explain how catalytic and catalytic support properties arise. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Silver structures fabricated in this way have shown robust long-term stability in high temperatures and oxidative conditions while maintaining their strong plasmon absorbance, suggesting excellent utility for use in SERS where surface oxidation and instability plague silver systems . Growth on the scaffold of γ-Al 2 O 3 not only provides a ready surface for nucleation but also exploits aluminum oxide’s relatively low work function (∼3.9–4.1 eV) when compared to face-centered cubic silver (∼4.5–7.4) . This interaction effectively protects the most easily oxidized [110] crystallographic face of the AgNP from significant oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Silver structures fabricated in this way have shown robust long-term stability in high temperatures and oxidative conditions while maintaining their strong plasmon absorbance, suggesting excellent utility for use in SERS where surface oxidation and instability plague silver systems . Growth on the scaffold of γ-Al 2 O 3 not only provides a ready surface for nucleation but also exploits aluminum oxide’s relatively low work function (∼3.9–4.1 eV) when compared to face-centered cubic silver (∼4.5–7.4) . This interaction effectively protects the most easily oxidized [110] crystallographic face of the AgNP from significant oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The model to represent the γ-alumina structure, Al 13 O 23 H 7 (Fig. 1), was constructed based on X-ray diffraction data [54,79] (Table S1, see Supporting Information), and it follows a spinel-like lattice, pointed by Ferreira and coworkers [64] as the most thermodynamically stable arrangement and considered in several studies [41,[56][57][58][59][60]. The aluminum cations and oxygen anions are arranged in three layers, in the DCD sequence, to expose the (110D) face mostly (Fig.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In this model, the (110) crystallographic plane, which the literature agrees is the most exposed (70 − 83%) [49][50][51], splits into two types of layers that are intercalated: the (110C), containing both Al o and Al t cations, and (110D), exhibiting only the octahedral aluminum. Models based on spinel lattice have been adopted in several studies [41,[52][53][54][55][56][57][58][59][60]. With the premise that Al 3+ cations occupying only spinel positions can be challenged [61], non-spinel models emerged, the most widespread one being that of Krokidis and coworkers [51,62,63].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that the surface morphological variations induce significant changes in electronic properties, e.g., work function and surface dipole, in connection of the surface oxidation level, by characterizing the influence of various surface formations in the frame of various surface models (e.g., dehydrated, partially hydroxylated, and terminated with aluminum atoms) through pseudopotential DFT simulations …”
Section: Introductionmentioning
confidence: 99%
“…10 Previously, we have shown that the surface morphological variations induce significant changes in electronic properties, e.g., work function and surface dipole, in connection of the surface oxidation level, by characterizing the influence of various surface formations in the frame of various surface models (e.g., dehydrated, partially hydroxylated, and terminated with aluminum atoms) through pseudopotential DFT simulations. 11 After publishing our paper 5 on the electronic properties of P-doped γ-Al 2 O 3 surfaces, we were motivated to determine the nature of the arrangement and local atom-level structure of P on γ-Al 2 O 3 . Since grain boundaries (e.g., as exemplified by SEM images) as well as other P−O−P bonding motives (such as P−O−P chains) play a role in the surface's catalytic and mechanical properties, 12−14 we embarked additional in-depth studies by considering new 72 distinct surface models based on the previous model calculations (O and OH terminated structures).…”
Section: Introductionmentioning
confidence: 99%